Associations Between Altered Cerebral Activity Patterns and Psychosocial Disorders in Patients With Psychogenic Erectile Dysfunction: A Mediation Analysis of fMRI - Yin, Tao; Liu, Qi; Ma, Ziyang; Li, Zhengjie; Sun, Ruirui; Ren, Feiqiang; Li, Guangsen; Huang, Xiaopeng; Chang, Degui; Zhang, Peihai (Frontiers in Psychiatry, 2020)
Previous studies had illustrated the significant neural pathological changes in patients with psychogenic erectile dysfunction (pED), while few works focused on the neural underpinning of the psychosocial status in patients with pED. This study aimed to investigate the associations among the altered cerebral activity patterns, impaired erectile function, and the disrupted psychosocial status in patients with pED. Thirty-two patients with pED and 28 healthy controls (HCs) were included. The amplitude of low-frequency fluctuations (ALFF), region-of-interest-based functional connectivity (FC), as well as Pearson correlation analyses and mediation analyses between neuroimaging outcomes and clinical outcomes were performed. Compared to HCs, patients with pED manifested lower erectile function, disrupted psychosocial status, as well as decreased ALFF in the left dorsolateral prefrontal cortex (dlPFC), and reduced FC between the left dlPFC and left angular gyrus, and left posterior cingulate cortex (PCC) & precuneus which belonged to the default mode network (DMN). Moreover, both the ALFF of the left dlPFC and FC between the left dlPFC and left PCC & precuneus were significantly correlated with the sexual function and psychosocial status in patients with pED. The disrupted psychosocial status mediated the influence of atypical FC between dlPFC and DMN on decreased erectile function. This study widened our understanding of the important role of psychosocial disorders in pathological neural changes in patients with pED.